Gullah Spirituals : The Sound of Freedom and Protest in the South Carolina Sea Islands - Crawford, Eric Sean (Book collections on Project MUSE., 2021)
"Eric Sean Crawford, associate professor of music and director of the Joyner Institute for Gullah and African Diaspora Studies at Coastal Carolina University, examines the history and diffusion of Gullah spirituals, an important and at times overlooked aspect of Gullah culture in the Lowcountry and Sea Islands of South Carolina and Georgia. Crawford's work focuses primarily on the South Carolina sea island of St. Helena in Beaufort County. While much has been done to study, preserve, and interpret Gullah culture, Crawford writes, "the shouting and rowing songs, containing the strongest West African retentions, are mostly lost and forgotten. This book illuminates the remarkable history, survival, and influence of this island's music since the earliest recordings in the 1860s." While Crawford's focus may be the St. Helena spirituals, his study is not limited only to that one place. Instead he examines the diffusion and impact of the music and culture that emanated from this one small island community. He follows the Gullah spirituals through to the musical arrangements of the famed Hampton Singers and later shows how the songs served as a rallying point and cultural bridge, helping to build support for America's involvement in World War I and as a way of easing racial tensions both at home and abroad. He shows how patriotic texts and themes were added to the spirituals and helped to make them popular wartime songs. Hampton University folklorist Natalie Curtis, for example, used the melody from the St. Helena spiritual "Ride On, Jesus" in her wartime anthem "Hymn of Freedom," which was sung not only in churches of the time, but also to gatherings of American soldiers mobilizing for war. Part of the goal of the US Army in choosing the song was to build African American support for the war, and also ease racial tensions within the (still segregated) ranks. Later, civil rights activists in the 1950s and 60s would find their own spiritual and political uses for the songs, as many were rediscovered and disseminated throughout the country as protest songs. The songs were not reimagined as protest songs, but rather had always been, and Crawford traces this long trajectory "from their beginnings in West Africa and later oppression by white missionaries to their height as songs for social change and black identity in the twentieth century." Crawford--an ethnomusicologist by training--relies not only upon archival records, but also conducted his own fieldwork, personal recordings, and oral interviews to develop his understanding of St. Helena and its music. His work, however, diverges from these earlier studies in its attempt to tell the stories not only of the music, but also of the music makers. This includes song leaders Minnie Gracie Gadson and Deacon James Garfield Smalls, who Crawford discusses in Chapter 7 and who both shared their own knowledge and memory of the St. Helena spirituals with Crawford during his time conducting field recordings on the island. Finally, Crawford includes an appendix with more than fifty transcriptions of St. Helena spirituals, many no longer performed and more than half derived from his own transcriptions completed during his fieldwork. The "Gullah Songbook," as he calls it, includes notations on Gullah terminology and phrasing that is provided by educator/author/television personality Ron Daise, who was the receipient for the 2019 South Carolina Governor's Award for his work preserving and disseminating Gullah culture"--